Memecah Siklus Kematian Keluarga : Analisis Kebijakan Kriminal Jepang terhadap Familicide di Masyarakat Urban - Zul Khaidir Kadir (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Familicide or murder of a nuclear family member. Urbanization in Japan has exacerbated the risk of familicide by changing patterns of social interaction and increasing life stress. Unfortunately, Japan's criminal policy still has weaknesses in detecting and preventing familicide. This study aims to explore the phenomenon of familicide in urban Japanese society through a critical analysis of existing criminal policies. This study uses a qualitative research method with a conceptual approach. The data collection method was collected using library research, then analyzed using qualitative methods and presented descriptively. The results of the study show that although the crime rate in Japan is relatively low, familicide remains a crucial issue that reveals fundamental weaknesses in the country's criminal policy. The legal approach that emphasizes post-incident responses, without being supported by adequate early prevention mechanisms, indicates an urgent need to reform the policy. Reforms must include proactive efforts to detect potential risks and implement coordinated interventions to prevent violence.